Impact of users' communities on broadband economics - Albert Domingo; Miquel Oliver (International Telecommunications Society (ITS), 2014)
Both users and operators are aiming for faster networks to host higher-quality contents. Legacy infrastructure models are still mainly based into facilities investment competition. The large investment to deploy a new network into the market has been a huge barrier for new entrants and it has moved regulators to favor infrastructure sharing and unbundling models to seek for competition. Moreover, the in-building deployment problems and the high costs of civil-works are hindering the optical fiber deployment to the home. On the other hand, the high demand for broadband creates new consumer habits towards digital contents and does not only rely on the network access technology to get connected. This need brings new opportunities for more innovative deployment models. This paper estimates the impact of having the end-users more actively involved in the deployment of fiber networks to reduce the overall investment. The techno-economic model drawn in this paper is based in the self-aggregation of users to share a broadband connection. More precisely, the model consists of a neighboring community of users that decides to build their own in-building access network to share a single broadband Internet connection. Services that are offered over the top of the network are contracted individually by end-user. The model allows comparing the effect of users contracting their Internet access in an aggregated way (at community/building level) in a highly competitive scenario. As noticed above, the expected effect of the involvement of users as a key element of a fiber network is to lower the overall investment up to a 45% mainly sustained by communities that will afford the in-building access network costs. The article analyzes the effect of users sharing a single connection that can lead to operator's reducing the risk and the length of the investment. It has been measured the investment length in terms of positive net present value, ROI over a certain interest rate and the payback period as the main indicators to explore how the higher engagement affects the deployment model in terms of risks and returns. In some cases, the investment periods increase by a factor of three or even can become non-sustainable if there is the pricing strategy ignores the aggregated demand. In addition to the new access network scenario, the model has implications on pricing, which directly affects the return of investment from the operator's side. In that way, the paper also compares the effect of keeping the same pricing scheme for individual and user-aggregate retail offer, to another pricing scheme that differentiates the offers for single users and communities.
Keywords: 330; Broadband; Techno-economic; FFTH; FTTH; Statistical multiplexing